PERAN SERTA MASYARAKAT DALAM UPAYA PENCEGAHAN DAN PEMBERANTASAN TINDAK PIDANA KORUPSI DALAM PRESPEKTIF UU NO 19 TAHUN 2019 TENTANG KOMISI PEMBERANTASANTINDAK PIDANA KORUPSI - Muhammad Aminudin, Muhammad Aminudin; Muhammad Sadi Is; Conie Pania Putri (Universitas Kapuas, 2024)
The crime of corruption is an Extra Ordinary Crime becoming the greatest enemy of the country and must work together to prevent and combat corruption. Fighting corruption is not just through law enforcement but preventive measures are crucial. Efforts to raise awareness of the issue of corruption must involve the role and society at large. To search, obtain and provide information on alleged corruption offences to law enforcement authorities. The issue in this study is how the rule of law regulates the role and society in the prevention and suppression of corruption crimes in Indonesia and the factors that influence the role as well as the society in preventing and suppressing corruption crime in Indonesia. This type of research is included in the study of normative law.The specification of this study is descriptive. The data sources used are voluntary, primary, and tertiary data. The data collection tool is library research. The data analysis technique used is qualitative analysis. Results in this study The role of the public in the efforts to prevent and combat corruption is essential in the fight against corruption crimes, the public must participate because of two things: the public as a victim and the society as a component of the state. Role forms and society is by dominating the role and society in efforts to prevent and combat corruption as regulated in the laws, namely the Law No. 31 Year1999 Jo Law No. 20 of 2001 on the Suppression of Criminal Acts of Corruption and Government Regulations of the Republic of Indonesia No. 43 Year 2018 on the Rules of Implementation of Roles and Society Awards in Prevention and Combating Corruption. The role as well as the community in the prevention and suppression of corruption crimes has not been performed effectively due to several factors, including legal factors, law enforcement factors, means and means factors, community factors and cultural factors. The recommendation given to the Government and the Council of Representatives of the People as the legislator is advised to make regulations specifically for the setting of roles as well as arrangements in the prevention and suppression of corruption crimes, further to socialize continuously to all elements of the society against such regulations, in cooperation with all institutions, universities, community organizations, stake holders etc., so that the public becomes aware and cares and can play a role in the preventing and suppressing corruption crime.